2013
DOI: 10.1074/jbc.m113.483909
|View full text |Cite
|
Sign up to set email alerts
|

The Herbal Compound Cryptotanshinone Restores Sensitivity in Cancer Cells That Are Resistant to the Tumor Necrosis Factor-related Apoptosis-inducing Ligand

Abstract: Background: Development of resistance is major problem in TRAIL anti-cancer therapy. Results: Cryptotanshinone induces death receptor 5 via ROS signaling and therefore enhances TRAIL-induced apoptosis. Conclusion: Cryptotanshinone restores TRAIL sensitivity in TRAIL-resistant cancer cells. Significance: We demonstrate a novel TRAIL-enhancing action by natural compound cryptotanshinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Similar with previous reports that CPT had antitumor function in vitro for many kinds of tumor cells (Park et al, 2013;Tse et al, 2013), our results also showed that CPT inhibited the proliferation of breast cancer cells (MCF7) in vitro. To further identify the antitumor activity of CPT in vivo, C57 mice all injected with 1×10 6 MCF7 cells, and then treated with CPT or Taxol since day 5, respectively.…”
Section: Cpt Inhibits Tumor Growth In Vivosupporting
confidence: 91%
“…Similar with previous reports that CPT had antitumor function in vitro for many kinds of tumor cells (Park et al, 2013;Tse et al, 2013), our results also showed that CPT inhibited the proliferation of breast cancer cells (MCF7) in vitro. To further identify the antitumor activity of CPT in vivo, C57 mice all injected with 1×10 6 MCF7 cells, and then treated with CPT or Taxol since day 5, respectively.…”
Section: Cpt Inhibits Tumor Growth In Vivosupporting
confidence: 91%
“…Thus, recently several natural compounds such as quercetin [33], curcumin [34], artepillin C [35], azadirone [36], emetine [37], crytotanshinone [38] and salirasib [39] are attractive as TRAIL sensitizers in many cancers. In the current study, we provide evidences that Tanshinone I sensitizes the prostate cancer cells to TRAIL induced apoptosis via upregulation of miR 135a-3p mediated DR5.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, these enclosed multiple kinase inhibitors targeting PKC (Gillespie et al, 2005), c-Kit (Hamai et al, 2006), IKK/NF-B , PI3K/Akt and MAP kinases . Also inhibitors of potassium channels (Quast et al, 2012;Suzuki et al, 2012), cellular metabolism (Liu et al, 2009;Qin et al, 2010), HDAC (Zhang et al, 2003) and COX-2 (Tse et al, 2014) were effective as well as natural compounds as picropodophyllin (Karasic et al, 2010), indirubin (Berger et al, 2011) and cryptotanshinone (Tse et al, 2013) or inorganic compounds as sodium arsenite (Ivanov and Hei, 2006;Ivanov and Hei, 2011). Due to this extremely high diversity, the pathways to melanoma sensitization for TRAIL remained elusive.…”
Section: Discussionmentioning
confidence: 99%